Methods of economical and financial estimation of the public investments in environmental protection branch - Rudnicki, Maciej (Studia Ecologiae et Bioethicae, 2005)
Nowadays, the realization of public, infrastructural investments in the area of environmental protection, is inseparably connected with financing them from various sources, public and private. The majority of funds which finance the investments like this, have very strict criterions of economical and financial evaluation of investment project. Although the public proecologic infrastructural investments concern the area of public services, they are treated like typical economical undertakings by financial institutions. Often , it turns out that well prepared and well organized undertaking does not meet the economical or financial demands of the fund which finances the investment. It is worth, then , to pay attention to some issues about criterions of economical and financial evaluation which are used in respect of public, infrastuctural, proecological investments. The author focused on criterions which are universal so that they recognized and used by many financial institutions and European Committee, European Investment Bank and National Fund of Environmental Protection and Water Economy.